Pengaruh Citra Merek, Kualitas Produk, dan Gaya Hidup terhadap Keputusan Pembelian Iphone di Kabupaten Bogor - Rezha Irsyadul Anam; Dedy Tri Cahyono; Mimin Rukmini; Didin Samsudin; Siana Ria (Pusat Riset dan Inovasi Nasional, 2025)
A brand is the identity and characteristic of a product, whether goods or services, that influences consumer decisions when choosing which product to use. Meanwhile, product quality refers to the consumer's evaluation of the advantages or special features of the product. In highly competitive markets like the smartphone industry, both brand and quality play crucial roles in attracting consumer attention. The smartphone market is currently filled with various brands competing for consumer attention, resulting in intense competition. According to data from the International Data Corporation (IDC), iPhone is one of the brands with a significant market share, demonstrating its ability to compete with other competitors. The success of the iPhone is not only driven by high product quality but also by its well-established brand image, which is widely recognized by consumers. However, competition in the smartphone market is not limited to big brands but also includes new manufacturers trying to capture consumer attention by offering various features and more affordable prices. The main issue in this research is the high level of competition in the smartphone category, indicating that this market is highly potential, with many consumers having multiple options. In this context, consumers are very selective and consider various factors, such as quality, price, and brand reputation, before making a purchasing decision. Therefore, smartphone manufacturers are required to be more meticulous in understanding consumer needs and desires. They must deliver innovative products that align with current trends and offer quality that meets consumer expectations. Manufacturers who can adapt to consumer preferences and maintain high product quality will have a significant opportunity to remain competitive and dominate the market in the increasingly competitive future.